Application of short time series analysis for the hydrodynamic characterization of a coastal karst aquifer: the Salento aquifer (Southern Italy). Issue 2 (23rd February 2022) - Balacco, Gabriella; Alfio, Maria Rosaria; Parisi, Alessandro; Panagopoulos, Andreas; Fidelibus, Maria Dolores
Abstract: Daily precipitation and groundwater level data, registered at 7 rain gauge stations and 11 monitoring wells in the Salento coastal karst aquifer (Southern Italy) were subject to short time series analyses to evaluate the hydrodynamic response of the aquifer. Results show that the Salento karst system has in general great storage capacity, which suggests a poor degree of aquifer karstification, and dominance in the permeability structure of not well-developed hierarchical karst networks. Baseflow generally dominates on quick flow, which only occasionally occurs. The dominant hydraulic behaviour is unimodal baseflow with a bimodal baseflow and quick flow one from time to time. Some local specific features, which emerge depending on the rainfall frequency and depth, and the geological and structural characteristics, point out that some components of the permeability structure, as the epikarst and major faults, only activate depending on the characteristics of the input. The study is novel because the analyses concerned specific sets of hydrological years from 2007 to 2011; also, because the analysis was conducted for a coastal karst aquifer of significant size, characterized by a regional groundwater flow system with an unsteady lower boundary, without inland freshwater springs, and significant exploitation by wells. HIGHLIGHTS: Short time series analyses between precipitation and groundwater level were applied to evaluate the hydrodynamic response of a coastal karst aquifer with a regional flow system. Results reveal a great storage capacity suggesting a not well-developed hierarchical karst networks. Rainfall intensity and frequency influence this hydrological system triggering hydrodynamic mechanisms at the epikarst and unsaturated zones. Graphical Abstract